Can the Weight Reduction Program Improve Obese Thai Adolescents’ Body Mass Index and Autonomous Motivation? - Kanlayanee, No-In; Tuicomepee, Arunya; Jiamjarasrangsi, Wiroj; Sithisarankul, Pornchai (Journal of Nepal Paediatric Society, 2017)
Introduction: Overweight and obesity has impacted both the physiological and psychological health of children and adolescents. Evidence of cross-cultural studies has showed mixed results regarding weight reduction program (WRPs) based on self-determination theory (SDT) and social cognitive theory (SCT) affecting students with overweight and obesity. This study examined the effectiveness of a WRP on body mass index (BMI) and autonomous motivation in overweight and obese Thai adolescents. Material and Methods: An experimental study with intervention and control groups was employed. Participants were 304 Thai obese 7th- to 12th-grade students, ranging in age from 12 to 19 years. The intervention group was assigned to a program based on SDT and SCT, consisting of (1) a 12-week weight control phase and (2) a 12-week follow-up phase. The control group was assigned to a general health education program. The data were collected via psychometric questionnaires and anthropometric data. Results: There were no statistical differences in adjusted means of BMI and autonomous motivation of physical activity and dietary intake occurred among participants in the two groups. Compared to those in the control group, participants in the intervention group showed a 0.4 smaller increase in BMI and a 0.4 greater decrease in autonomous motivation of dietary intake. Conclusion: The WRP based on SDT and SCT showed no apparent effectiveness in improving BMI or autonomous motivation among these participants. Future studies should incorporate program that effectively harmonize with core school teaching activities and schedules.